Pengaruh Motivasi Kerja, Burn Out Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Victory Retalindo Jakarta Pusat - Aldian Ramadhan; Rahmayanti Tumanggor (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This study aims to determine the influence of work motivation, burnout, and work discipline on employee performance at PT Victory Retalindo Central Jakarta. Employees are strategic assets in an organization, and the success of a company is largely determined by the quality of employee performance. This research uses a quantitative approach with an associative method. The sample consisted of 60 respondents who are employees of PT Victory Retalindo. Data collection was carried out through questionnaires, and data analysis employed validity and reliability tests, classical assumption tests, multiple linear regression, as well as partial and simultaneous hypothesis testing. The results show that work motivation has a positive and significant effect on employee performance. Meanwhile, burnout does not have a significant effect, but work discipline has a positive and significant effect. Simultaneously, work motivation, burnout, and discipline have a significant effect on employee performance. These findings emphasize the importance for companies to pay attention to internal employee factors to improve overall performance. This study is expected to serve as a reference in developing more effective human resource management strategies Keywords: Work Motivation, Burnout, Work Discipline, Employee Performance.